ANALISIS FAKTOR YANG MEMPENGARUHI HASIL BELAJAR MAHASISWA S1 PGSD BIDANG ILMU DAN MAHASISWA S1 PGSD REGULER TERHADAP MATA KULIAH TUGAS AKHIR PROGRAM (TAP) DI UPBJJ SERANG - Prayekti Prayekti (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Program Final Task (PFT) is the subject which should be taken by undergraduate student of PGSD FKIP of Open University on the Last Semester if the student has taken 140 semester credit system (SCS), special for undergraduate student of regular PGSD should take the Program Final Task (PFT) on semester X and for undergraduate student of PGSD with science field should take Program Final Task (PFT) on semester two. Factor analysis students for final test on PFT with the other two groups. Result study showed that (1) there is significant differences of motivation score between undergraduate the other student groups, average of motivation score of undergraduate student group of PGSD with Science Field is higher that undergraduate student of regular PGSD; (2) Assumption with Glejser test were obtained that independent variable is insignificant effected for absolute residual, then the assumption no heteroscedasticity is fulfilled,; (3) Simultaneous test result showed that Ho for simultaneous test is rejected because F-count value to be greater that F-table and the significance is less that 0,05. (4) self-sufficient student gave positively effect for PFT value (Y). Higher self-sufficient student, higher PFT value. Keywords: PFT, self-sufficient, motivation, learning aid.